Margaret Chase Smith Library: Supporting Primary Source Research the Archive - Potter, Nicole (Maine Policy Review, 2024)
Bringing students into close contact with the primary source materials held by the Margaret Chase Smith Library can help them think more deeply about history and prompt deeper curiosity. Library staff have developed a variety of learning opportunities that prepare students with contextual information, enable them to observe and respond to archival materials, and promote the importance of them developing their own lines of inquiry and speculation.